Forest loss in Malawi: how having women at the table affected debates and decisions about solutions – research - Kosec, Katrina; Clayton, Amanda; Robinson, Amanda Lea; Dulani, Boniface (The Conversation, 2025)
Around the world, climate change is being tackled, not just in parliaments and global summits, but also in villages and farming communities. In these local spaces, lives and livelihoods depend directly on natural resources, and decisions are often made in groups.